2013
DOI: 10.1167/iovs.13-12793
|View full text |Cite
|
Sign up to set email alerts
|

1,2-Naphthoquinone Stimulates Lipid Peroxidation and Cholesterol Domain Formation in Model Membranes

Abstract: These data suggest a novel mechanism for naphthalene-induced cataract, facilitated by the direct effects of 1,2-NQ on lipid peroxidation and cholesterol domain formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…Second, existing methods, because of the presence of other domains in intact membranes, could not discriminated CBDs. Our measurements (Mainali et al, 2013b; Raguz et al, 2011a, b) and data from the literature (Jacob et al, 2013; Jacob and Mason, 2005; Jin et al, 2018; Litz et al, 2016) indicate that, in model membranes, when the Chol content is close to or exceeds the Chol solubility threshold in PL bilayers, CBDs are always present. Additionally, the formation of CBDs precedes the formation of Chol crystals (Mainali et al, 2013b).…”
Section: Discussionsupporting
confidence: 60%
“…Second, existing methods, because of the presence of other domains in intact membranes, could not discriminated CBDs. Our measurements (Mainali et al, 2013b; Raguz et al, 2011a, b) and data from the literature (Jacob et al, 2013; Jacob and Mason, 2005; Jin et al, 2018; Litz et al, 2016) indicate that, in model membranes, when the Chol content is close to or exceeds the Chol solubility threshold in PL bilayers, CBDs are always present. Additionally, the formation of CBDs precedes the formation of Chol crystals (Mainali et al, 2013b).…”
Section: Discussionsupporting
confidence: 60%
“…To conclude, we reiterate that the proposed hypothesis has already been tested in its basic sense. The published experimental results show that (1) formation of CBDs in liposomal membranes precedes formation of Chol crystals (e.g., [17,18,20,30,31]), and (2) Chol crystals can be formed from membrane Chol (without the external addition of Chol) when the Chol solubility threshold in the membrane is decreased, for example, by lipid peroxidation [21][22][23]. Based on the saturation recovery EPR technique, we are planning to design an experimental procedure to quantitatively estimate the average amount of Chol in a CBD at the saturation threshold in bilayers made of polyunsaturated phospholipids (before peroxidation).…”
Section: Discussionmentioning
confidence: 99%
“…[37]. It has been also shown that phospholipid peroxidation decreases to a considerable extent the Chol concentrations at which formation of CBDs [21,22] and Chol crystals [31] are initiated. Peroxidation mainly involves the polyunsaturated chain and introduces a hydroperoxide group into the chain at a double-bond position.…”
Section: Chol and Phospholipid Oxidation As Factors Affecting Chol Samentioning
confidence: 97%
See 1 more Smart Citation
“…In our portfolio experience, CP‐03504992 and CP‐642,931, but not its pharmacological pair, CP‐470,711, promoted cholesterol domain formation in rat brain sphingomyelin membranes (data not shown), suggesting disruptions on proper cholesterol biosynthesis and cholesterol domain formation as important independent contributors to cataract formation, which is a known feature of cataractous lenses (Jacob et al, ). Other known cataractogens such as U18666A and 1,2‐naphthoquinone, the reactive metabolite of naphthalene, also promote cholesterol domain formation through oxidative stress (Cenedella, ; Cenedella et al, ; Jacob, Aleo, Self‐Medlin, Doshna, & Mason, ).…”
Section: Discussionmentioning
confidence: 99%